Genome-Wide Identification of RNA Modifications for Spontaneous Coronary Aortic Dissection - Chai, Tianci; Tian, Mengyue; Yang, Xiaojie; Qiu, Zhihuang; Lin, Xinjian; Chen, Liangwan (Frontiers in Genetics, 2021)
RNA modification plays important roles in many biological processes such as gene expression control. Genetic variants that affect RNA modification may have functional roles in aortic dissection. The aim of this study was to identify RNA modifications related to spontaneous coronary artery dissection (SCAD). We examined the association of RNA modification-associated SNPs (RNAm-SNPs) with SCAD in summary data from genome-wide association study (270 SCAD cases and 5,263 controls) of European descent. Furthermore, we performed eQTL and pQTL analyses for the RNAm-SNPs using public available data. Functional enrichment and protein-protein interaction analyses were performed for the identified proteins. We found 11,464 unique RNAm-SNPs in the SCAD GWAS dataset and 519 were nominally associated with SCAD. Nine RNAm-SNPs were associated with SCAD at P < 0.001, and among them seven were m6A methylation related SNPs, one (rs113664950 in HLA-DQB1) was m7G-associated SNPs and one (rs580060 in the 3′-UTR of MRPS21) was A-to-I modification SNPs. The genome-wide significant SNPs rs3818978 (SCAD-association P = 5.74 × 10-10) in the 5′-UTR of MRPS21 was related to m6A modification. These nine SNPs all showed eQTL effects and six of them were associated with circulating protein or metabolite levels. The related protein coding genes were enriched in specific GO terms such as extracellular space, extracellular region, defense response, lymphocyte migration, receptor binding and cytokine receptor binding, and so on. The present study found the associations between RNAm-SNPs and SCAD. The findings suggested that RNA modification may play functional roles in SCAD.